Benefit-Sharing Mechanisms: An introduction to planning and implementation - Consorcio para el Desarrollo Sostenible de la Ecorregion Andina (CONDESAN, 2014)
Water is essential for all human life and the ecosystems that support us. Water is a fundamental human right - socially, economically and culturally important. For communities living in the Andean and Amazonian regions, this is especially true. Today these communities are facing three major water challenges as they fight to reduce poverty and protect their environment: